OPTIMIZING DIGITAL MARKETING AND FINANCIAL REPORTS WITH TAMANSISWA TEACHING: NGARTI NGRASA - Prasetya, Arief; Kejora Renaldi, Syaquina; Alvin Maharani, Az Zahra; Puspita Sari, Devita; Maria Wadon, Legio; Supardin, Lalu; Andleeb, Naima (EMPOWERING HUMANITY, 2024)
Community Service "Optimizing Digital Marketing and Financial Reports with Tamansiswa Teachings: Ngarti-Ngrasa" at UMKM Adrem Mawar Merah Mbak Tini in Piring II Village, Murtigading, Sanden, Bantul, focused on improving marketing strategies and financial management. The implementation method involves direct interviews with MSME owners to identify key problems, including a lack of understanding of marketing on online platforms and the complexity of financial reports. Interview results show that Adrem products are little known outside the Bantul area and experience difficulties in managing finances due to a lack of understanding of balance sheets and profit and loss statements. Therefore, the service team provides solutions through digital marketing materials and the preparation of effective financial reports. The aim of this program is to increase the visibility of Adrem products and increase the effectiveness of financial management, so as to improve the economy of these MSMEs.